2013
DOI: 10.1007/s00508-013-0407-2
|View full text |Cite
|
Sign up to set email alerts
|

Severity illness scoring systems for early identification and prediction of in-hospital mortality in patients with suspected sepsis presenting to the emergency department

Abstract: The in-hospital mortality of patients with severe sepsis and septic shock (SSSS) is high. In this study we examined the diagnostic and prognostic accuracy of the emergency severity index (ESI), the modified early warning score (MEWS), and the mortality in emergency department (ED) sepsis (MEDS) score. This is a single-centre, prospective and observational study of 151 consecutive patients presenting to the ED of the Nuremberg Hospital with suspected sepsis (age 68.3 ± 18 years, 54.3 % men, 45 % with SSSS, in-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
2
29
0
3
Order By: Relevance
“…Hence Geier F et. al. identi ed that ESI triage system has weakness with regards to early identi cation of patient with sepsis, however patient with septic shock are able to identi ed reliably as with our results 12 Our study showed that 11.6% of the patients were categorized as ESI III, which is a high number considering the signi cant mortality associated with sepsis and further studies are required to assess the factors associated with the variation in categorization of these patients in ESI III and above.…”
Section: Discussionsupporting
confidence: 55%
“…Hence Geier F et. al. identi ed that ESI triage system has weakness with regards to early identi cation of patient with sepsis, however patient with septic shock are able to identi ed reliably as with our results 12 Our study showed that 11.6% of the patients were categorized as ESI III, which is a high number considering the signi cant mortality associated with sepsis and further studies are required to assess the factors associated with the variation in categorization of these patients in ESI III and above.…”
Section: Discussionsupporting
confidence: 55%
“…Geier et al 15 evaluated the Emergency Severity Index (ESI) in a prospective study in patients with severe sepsis and septic shock. The working group found a sensitivity of 70.8%, the NPV was 62.3% and the LR– was 64%.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Therefore, it is pivotal to accurately predict prognosis of sepsis patients at different stages and to help optimize treatment options. There are few well-established scoring tools including APACHE II score, improved early warning score (modified early warning score, MEWS), and SOFA score, [9] which have been useful in predicting clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%